BEBERAPA FAKTOR YANG BERPENGARUH TERHADAP PROGRESIVITAS KELOMPOK TANI LAHAN PANTAI DI KABUPATEN KULON PROGO (THE FACTORS THAT INFLUENCE PROGRESSIVENESS OF COASTAL LAND FARMER GROUPS IN KULON PROGO REGENCY) - Redono, Cucuk (Politeknik Pembangunan Pertanian Yogyakarta-Magelang, 2006)
The objective of this study is to identify: (1) the factors which influenced the progressiveness of coastal land farmer groups in Kulon Progo Regency, (2) the most significant factor which influenced. The study was conducted at Kulon Progo Regency by taking 30 farmer groups in Temon Sub-Regency (15 groups/4 villages), Wates Sub-Regency (3 groups/1 village), Panjatan Sub-Regency (8 groups/3 villages), and Galur Sub-Regency (4 groups/2 villages). Analysis of descriptive, multiple linear regression, and path analysis are used in this study. The progressiveness of coastal land farmer groups in Kulon Progo Regency is influenced by the role of extension worker, groups leadership, cohesiveness of groups and the role of village government officer.